Symbolic or Substantive? Greenwashing and Environmental Disclosure Misalignment in Indonesian Banking - Netti Natarida Marpaung; Sugeng Wahyudi; Irene Rini Demi Pangestuti (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - This study investigates whether Environmental Disclosure Scores (EDS) accurately reflect actual environmental performance, as proxied by GHG emissions, in the Indonesian banking sector.Method - The research employs panel data analysis using 16 publicly listed Indonesian banks from 2009 to 2023. A random-effects regression is applied, followed by the construction of a binary Greenwashing Index (GWI) to identify misalignments between EDS and actual greenhouse gas (GHG) emissions.Main Findings - The findings indicate that EDS are not significantly associated with lower GHG emissions, suggesting a symbolic rather than substantive role. Although larger banks tend to emit more GHG, they are less likely to engage in greenwashing, likely due to greater regulatory scrutiny. In contrast, higher profitability increases greenwashing risk, while stronger capital adequacy reduces it.Theory and Practical Implications - The findings suggest that ESG reporting should be based on performance metrics rather than narrative disclosures to ensure accountability. Policymakers are encouraged to enforce independent environmental audits and adopt outcome-based ESG frameworks. Novelty - This study contributes a novel dual-approach Greenwashing Index to identify disclosure–performance misalignment, offering empirical insights for ESG research in emerging markets.